Evaluation of Blood and Cerebrospinal Fluid Biochemistry, Cytology and Haematological Parameters in Head-and-Eye Form of Malignant Catarrhal Fever in Cattle - Uzlu, Erdoğan; Erkılıç, Ekin Emre; Adali, Yasemen; Öğün, Metin; Sahna, Kezban; Eryeğen, Nilhan; Kirmizigul, Ali Haydar (My University, 2023)
In this study, it was aimed to examine the biochemical changes, hematological changes and cerebrospinal fluid (CSF) cytology and blood serum of cattle with head-eye form of Malignant Catarrhal Fever (MCF). For this pur- pose, 22 cattle diagnosed with \"head-eye form\" of MCF and clinically healthy 10 cattle were evaluated. Blood and cere- brospinal fluid (CSF) were collected from all cattle. In sera, AST, urea, glucose, CK (P<0.05), LDH levels (P<0.01) were found be high, ALT, ALP, cholesterol (P<0.05), Ca, total protein (P<0.01) and Mg, albumine and Fe levels (P<0.001) were found to be low in MCF group when compared to the control group. In CSF, Ca (P<0.01) and total protein levels (P<0.001) were found high glucose level (P<0.05) was found low in MCF group when compared to the control group. In haematology, some parameters were determined to be different between the groups. In cytological results of CSF in MCF group, polymorphonuclear leucocytes, lymphocytes, erytrocytes, macrophages and plasma cells were determined. In conclusion, since there were a limited number of studies examining biochemical, cytologic and hematological results of MCF especially in CSF, the results from our study were thought to be important for future stud- ies in which viral diseases affects the nervous system of cattles.
Keywords: CSF; cattle; cytology; haematology; malignant catarrhal fever; Biochemistry